2022
DOI: 10.1007/s40333-022-0064-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in diversity, composition and assembly processes of soil microbial communities during Robinia pseudoacacia L. restoration on the Loess Plateau, China

Abstract: Robinia pseudoacacia L. (RP) restoration has increased vegetation cover in semi-arid regions on the Loess Plateau of China, but ecological problems have also occurred due to RP restoration, such as reduced soil moisture. Further, it is still uncertain how microbial diversity, composition and assembly processes change with RP restoration in semi-arid regions. Therefore, amplicon sequencing of small subunit ribosomal ribonucleic acid (16S rRNA) and internal transcribed spacer (ITS) genes was performed to study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Previous studies have found positive [62,63] or negative [47,64] effects of vegetation restoration on fungal diversity. For example, the decrease in plant diversity in the sown treatments was followed by a decline in the diversity of plant litter and root exudates; a reduction in the heterogeneity of resources may induce a reduction in the fungal diversity [10,64].…”
Section: Effects Of Vegetation Restoration On the Soil Fungal Communi...mentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies have found positive [62,63] or negative [47,64] effects of vegetation restoration on fungal diversity. For example, the decrease in plant diversity in the sown treatments was followed by a decline in the diversity of plant litter and root exudates; a reduction in the heterogeneity of resources may induce a reduction in the fungal diversity [10,64].…”
Section: Effects Of Vegetation Restoration On the Soil Fungal Communi...mentioning
confidence: 89%
“…In addition, revegetation by the sowing of a single species led to a reduction in the diversity of bacteria which was determined by a reduction in the plant diversity [10]. Thus, the different effects of vegetation restoration on the bacterial community's diversity may be determined by the soil nutrient status [71,72], restoration vegetation selection [62,69,72], plant diversity level [10,71,73], and restoration time [62,73]. Previous results found that the bacterial community's structure is closely related to the soil's nutrients in artificial vegetation restoration [69,70].…”
Section: Effects Of Vegetation Restoration On the Soil Bacterial Comm...mentioning
confidence: 99%
“…In this study, microbial communities in class III showed higher connectivity and complexity than those in class I and class II, indicating that the complexity of the microbial networks tended to increase with forest age ( Table 3 and Figure 3 ), which led to higher community stability [ 66 ]. This finding may be attributable to the increase in plant diversity and nutrient content availability throughout their growth cycle [ 23 ]. Wang et al [ 16 ] have revealed that the complexity of the Pinus tabulaeformis bacterial networks tended to increase markedly from 15 years to 60 years [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In soil ecosystems, microbial species coexist in complex arrays through positive (e.g., symbiosis) and negative (e.g., competition) associations [ 17 , 18 ], which can regulate the microbial community structure and thus adjust the functions it provides to the ecosystem [ 19 , 20 ]. Co-occurrence networks are increasingly used to infer linkages among microbial species in many different environments, including the human gut [ 21 ], oceans [ 22 ], and soils [ 23 , 24 , 25 , 26 ]. Networks analyses can be instrumental in describing network topological properties and inferring community assembly processes [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the ratio of immigration/emigration influences community biodiversity. Differences in assembly between bacteria and fungi [59], heterotrophs and autotrophs [36], specialists and generalists [54], and abundant and rare taxa [60][61][62][63] influence community composition.…”
Section: Successional Trends In Community Assemblymentioning
confidence: 99%